1991
DOI: 10.3382/ps.0701390
|View full text |Cite
|
Sign up to set email alerts
|

Some Effects of Dietary Aluminum and Silicon on Broiler Chickens

Abstract: Experiments were conducted to determine whether dietary silicon will reduce the toxic effects of dietary aluminum on broiler chickens. The parameters measured were weight gain, feed efficiency, percentage bone ash, tibial dyschondroplasia, and the retention of calcium, phosphorus, and phytin phosphorus. Experiments 1 and 2 were conducted with casein and gelatin-based purified diets and Experiments 3 and 4 with corn and soybean meal-based practical diets. All experiments used day-old broiler cockerels and laste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 25 publications
1
23
0
1
Order By: Relevance
“…Each zeolite species has its own unique crystal structure and, hence, its own set of chemical and physical properties. Among many properties attributed to zeolites, most characteristics that relate to their effectiveness in animal nutrition are their ability to lose or gain water alternatively, and being capable of exchanging a variety of cations selectively without much major changes in their structure (Mumpton & Fishman, 1977;Waldroup et al, 1984;Elliot & Edwards, 1991;Mumpton, 1999;Shariatmadari, 2008;Safaeikatouli et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each zeolite species has its own unique crystal structure and, hence, its own set of chemical and physical properties. Among many properties attributed to zeolites, most characteristics that relate to their effectiveness in animal nutrition are their ability to lose or gain water alternatively, and being capable of exchanging a variety of cations selectively without much major changes in their structure (Mumpton & Fishman, 1977;Waldroup et al, 1984;Elliot & Edwards, 1991;Mumpton, 1999;Shariatmadari, 2008;Safaeikatouli et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Mineral metabolism and electrolyte balance largely regulate bone formation that would be linked to their primary action on mineral absorption, tissue distribution and excretion . On the other hand, it has also been reported that zeolites suppressed P utilization by forming an indigestible compound with P through its aluminosilicate component, increased Ca utilization (Elliot & Edwards, 1991) and had an indirect effect on P absorption and metabolism (Leach et al, 1990). Although several studies claimed that the addition of zeolites increased Ca utilization and the rate of bone ash deposition during growth Ballards & Edwards, 1988;Debeic, 1994;Zhang & Hung 1992;Rabon et al, 1995), other researchers reported no zeolite effect Elliot & Edwards, 1991;Gezen & Eren, 2002;Keshavarz & Mccormick, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Serum 1,25-(OH)2D3 düzeyleri 16. haftada sadece fitaz eklenen grupta diğer gruplardan daha yüksek, 8. haftada fitaz ve zeolit ilave edilen grupta diğer gruplardan daha düşük saptanmıştır (P<0.05).…”
Section: Mikrobiyal Fitaz İlaveli Yumurta Tavuğu Rasyonlarına D3 Vitaunclassified
“…However contradictory results were reported on growth performance [16] and bone ash content [19] . Discrepancies between the studies might be partially attributable to the type of zeolite, purity and physicochemical properties of the product used in the experiments [20] , supplementation level to the diets, and dietary calcium level [21] .…”
Section: Introductionmentioning
confidence: 99%
“…Clinoptilolite has a beneficial effect on tibia bone mineralization and calcium and phosphorus utilization in broiler chicks [13] . On the other hand, Elliot and Edwards [16] and Leach et al [17] reported that zeolites suppressed P utilization by forming an indigestible compound, and had an indirect effect on P absorption and metabolism.…”
Section: Introductionmentioning
confidence: 99%